Maps of time : an introduction to big history - Christian, David, 1946- (California world history library., 2011)
An introduction to a new way of looking at history, from a perspective that stretches from the beginning of time to the present day, Maps of Time is world history on an unprecedented scale. Beginning with the Big Bang, David Christian views the interaction of the natural world with the more recent arrivals in flora and fauna, including human beings. Cosmology, geology, archeology, and population and environmental studies--all figure in David Christian's account, which is an ambitious overview of the emerging field of "Big History." Maps of Time opens with the origins of the universe, the stars